1994
DOI: 10.1068/p230991
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Luminosity on Different Backgrounds and in Different Illuminations

Abstract: Observers were presented with target surfaces of varying luminance and asked to report whether they appeared luminous or opaque. In one experiment the targets were presented against three backgrounds, white, gray, and black. In another experiment the targets were presented within Mondrian patterns that were either brightly or dimly illuminated. The results indicate that, across a variety of conditions, a target begins to appear luminous when its luminance is about 1.7 times that of a surface that would appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 25 publications
2
73
2
Order By: Relevance
“…Across all experiments, the relative contrasts of the stimuli (stimulus luminance-background luminance) varied from 0.745 to 0.800. Depending on the contrast level, targets could appear self-luminous, (contrasts levels above 1.7), white (contrasts from 1.1 to 1.7), gray (contrasts from 0.5 to 0.9), or black (contrasts below 0.5), for the relatively simple stimulus configurations in these experiments (Bonato & Gilchrist, 1994;Heggelund, 1974). The contrast levels were chosen to give the appearance of gray surfaces that were darker than the background and to avoid the percepts of luminous white and black objects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across all experiments, the relative contrasts of the stimuli (stimulus luminance-background luminance) varied from 0.745 to 0.800. Depending on the contrast level, targets could appear self-luminous, (contrasts levels above 1.7), white (contrasts from 1.1 to 1.7), gray (contrasts from 0.5 to 0.9), or black (contrasts below 0.5), for the relatively simple stimulus configurations in these experiments (Bonato & Gilchrist, 1994;Heggelund, 1974). The contrast levels were chosen to give the appearance of gray surfaces that were darker than the background and to avoid the percepts of luminous white and black objects.…”
Section: Methodsmentioning
confidence: 99%
“…or a change in the reflectance of the background. A study by Bonato and Gilchrist (1994) suggested, however, that observers interpret the absolute change of luminance across the background as a change of illumination. Using a stimulus configuration similar to this experiment, a single central target either on a large background surround or on a ganzfeld surround, they found that the background tended to maintain an appearance of white despite large changes in the absolute luminance of the background and in the relative contrast of the background with the target.…”
Section: Experiments 4amentioning
confidence: 99%
See 1 more Smart Citation
“…Unmatchable surfaces have sometimes been reported when a simple disk-ring arrangement has been compared with a more complex stimulus (Bruno, 1992;Bruno, Bernardis, & Schirillo, 1997). Most important, a number of investigators have noted that within the same stimulus space, some surfaces can appear definitely too bright, almost self-emitting, for matching on a decremental scale to be possible (Bonato & Gilchrist, 1994;Heinemann, 1955;MacLeod, 1947). This peculiar mode of appearance has been called fluorescence (Evans, 1959(Evans, , 1974 or, more recently, superwhite (Gilchrist et al, 1999).…”
Section: Measuring Surface Colormentioning
confidence: 99%
“…The relationship of targets with their background can affect both their appearance (Bonato & Gilchrist, 1994;Heggelund, 1974) and detectability (Boynton, Ikeda, & Stiles, 1964;Ehrenstein & Spillmann, 1983;Patel & Jones, 1968;Short, 1966). Consequently, two sets of observations were gathered, one with the simulated reflectances (and therefore the luminances) of both targets greater than that of the background and the other with the targets' simulated reflectances (and luminances) lower than that of the background.…”
Section: Overview Of Experimentsmentioning
confidence: 99%